Research of Influence of Creativity and Innovativeness on Development - Marek Brzeziński; Katarzyna Czop; Agnieszka Leszczyńsk (Contemporary Economics)
In the article the research of relations between creativity, innovativeness and development of organization was presented. In the light of result there is significant influence of innovativeness on development of organization and inversely dependency in the case of its potential. On the results of organization affects innovativeness, but creativity, as pra-source, affects directly or indirectly on all variables.